Website Go-Ramp: Rancang Bangun Sistem Ramp Check Transportasi Berbasis Web Dengan Integrasi Terpusat - Putri, Anisa; Haidar, M. Faris; W.W, Oktafadion W.W; Syifa F.P.S, Adinda; Ahmad F, Zufar; Roviurrahman, Habib; Tsani, M. Rifqi (Jurnal Pendidikan Vokasi Otomotif, 2024)
Ramp check is a process used to ensure that vehicles used for public transportation meet safety requirements. The ramp check procedure has developed from a manual technique to a digital system thanks to advances in technology, and can now be done through a platform called ramp check online or Go Ramp . By utilizing information technology, this approach makes vehicle inspections more transparent, accurate and efficient. Go Ramp enables fast and real-time verification of vehicle technical specifications, validates administrative documents, and assesses the driver's physical well-being. Time efficiency, data quality, process transparency, ease of access for vehicle owners, and centralized monitoring by relevant authorities are some of the main advantages of this system. Online ramp inspection is expected to improve traffic safety, reduce accident rates, and ensure that all cars on the road comply with established safety regulations. Go Ramp is a pioneer in modernizing transportation management and improving road safety in the digital era by implementing digital technology in ramp checks. Keywords: Ramp check, Go Ramp, Digital